Hybrid model for optimization of ambulance allocation relocation in smart cities - Rafiqa Dewi (Institute of Computer Science (IOCS), 2023)
To increase the percentage of survival of citizens both in normal times and in times of emergency or Emergency Medical Services (EMS) which is one of the main pillars in a smart city, among the most important is ambulance management. A hybrid model between LR-MEXCLP is a model that combines local activity estimation with the TIMEXCLP model by achieving maximum coverage on MEXCLP which then this hybrid model can lead in solving a series of ambulance facility placement problems more accurately. This model was developed by establishing an integration model between the ability to estimate local activity and maximum completion coverage and with the shortest response time, so as to create a reliable ambulance service in a smart city.